Proceedings of the 3rd International Conference on Higher Education Advances 2017
DOI: 10.4995/head17.2017.5612
|View full text |Cite
|
Sign up to set email alerts
|

Cracking the Cocoon: Promoting Self-Directed Lifelong Learning in EFL Pre-service Teachers in Chile Through the Guided Use of Social Media Tools

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Relevant research also discussed the relationship between self-directed learning and the use of ICT. ICT has repeatedly been claimed to provide great opportunities for building processes through self-directed learning (Delen, Liew, & Willson, 2014;Rampai, 2013;Sumuer, 2018), thus cultivating lifelong learners (Paula & Danisa, 2017). Specifically, the use of technology has a direct positive relationship with engagement and self-directed learning.…”
Section: Student Perception Towards Ictmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant research also discussed the relationship between self-directed learning and the use of ICT. ICT has repeatedly been claimed to provide great opportunities for building processes through self-directed learning (Delen, Liew, & Willson, 2014;Rampai, 2013;Sumuer, 2018), thus cultivating lifelong learners (Paula & Danisa, 2017). Specifically, the use of technology has a direct positive relationship with engagement and self-directed learning.…”
Section: Student Perception Towards Ictmentioning
confidence: 99%
“…However, recent studies have revealed that there is no standard framework to indicate factors that successfully contribute towards lifelong learning (Arrigo, Hulme, Sanchez, & Kismihok, 2013;Dolan, 2012). Prior investigation suggested potential factors that influence successful lifelong learning, such as self-directed learning (Atta & Alghamdi, 2018;Van Rensburg & Botma, 2015), social networking (Haseski, Şahin, Yilmaz, & Erol, 2014;Jaleel & Om, 2017) and perception towards ICT (Paula & Danisa, 2017). Thus, individuals with high levels of self-directed learning, social networking and positive perception towards ICT usually reveal a high degree of lifelong learning.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant research also discussed the relationship between self-directed learning and the use of ICT. ICT has repeatedly been claimed to provide great opportunities for building processes through self-directed learning (Delen, Liew, & Willson, 2014;Rampai, 2013;Sumuer, 2018), thus cultivating lifelong learners (Paula & Danisa, 2017). Specifically, the use of technology has a direct positive relationship with engagement and self-directed learning.…”
Section: Student Perception Towards Ictmentioning
confidence: 99%
“…However, recent studies have revealed that there is no standard framework to indicate factors that successfully contribute towards lifelong learning (Arrigo, Hulme, Sanchez, & Kismihok, 2013;Dolan, 2012). Prior investigation suggested potential factors that influence successful lifelong learning, such as self-directed learning (Atta & Alghamdi, 2018;Van Rensburg & Botma, 2015), social networking (Haseski, Şahin, Yilmaz, & Erol, 2014;Jaleel & Om, 2017) and perception towards ICT (Paula & Danisa, 2017). Thus, individuals with high levels of self-directed learning, social networking and positive perception towards ICT usually reveal a high degree of lifelong learning.…”
Section: Introductionmentioning
confidence: 99%